PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA KANTOR PUSDIKLAT TENAGA ADMINISTRASI KEMENAG-RI – TANGERANG SELATAN - Fani Dewi Fitria; Theobaldus Boro Tura (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the influence of work motivation and physical work environment on employee performance at the Training and Development Center for Administrative Personnel, Ministry of Religious Affairs of the Republic of Indonesia – South Tangerang. This research is a associative quantitative study utilizing data collection techniques such as observation, interviews, and questionnaires. The population of this study consists of all employees at the Training and Development Center for Administrative Personnel, Ministry of Religious Affairs of the Republic of Indonesia – South Tangerang, totaling 63 employees. The sampling technique used is saturation sampling, meaning all employees were included as the sample for this study, amounting to 63 individuals. The data analysis techniques include descriptive analysis, instrument testing, classical assumption testing, multiple linear Regression analysis, correlation coefficient testing, determination coefficient testing, as well as t-tests and F-tests, with the aid of SPSS version 27 software. The results of this study indicate that there is a significant influence of Work Motivation (X₁) on Employee Performance (Y) at the Training and Development Center for Administrative Personnel, Ministry of Religious Affairs of the Republic of Indonesia – South Tangerang. This is evident from the t-test results, where tcalculated>ttable (5.621>2.000), which is further supported by a significance value of 0.000<0.05. Therefore, H₀₁ is rejected, and Hₐ₁ is accepted. Additionally, there is a significant influence of the Physical Work Environment (X₂) on Employee Performance (Y) at the same institution. This is shown by the t-test results, where tcalculated>ttable (3.525>2.000), and a significance value of 0.000<0.05. Thus, H₀₂ is rejected, and Hₐ₂ is accepted. Finally, there is a joint influence of Work Motivation (X₁) and Physical Work Environment (X₂) on Employee Performance (Y) at the Training and Development Center for Administrative Personnel, Ministry of Religious Affairs of the Republic of Indonesia – South Tangerang. This is demonstrated by the F-test results, where Fcalculated>Ftable (31.450>3.15), further confirmed by a significance value of 0.000<0.05. Hence, H₀₃ is rejected, and Hₐ₃ is accepted.